2004
DOI: 10.1038/sj.bjp.0705704
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin inhibits airway microvascular leakage induced by HCl intra‐oesophageal instillation

Abstract: 1 Gastro-oesophageal acid reflux may cause airway responses such as cough, bronchoconstriction and inflammation in asthmatic patients. Our previous results suggest that microvascular leakage induced, in the guinea-pig airways, by intra-oesophageal hydrochloric acid (HCl) infusion was mainly dependent on the release of tachykinins. Nociceptin, an endogenous ligand of the opioid receptor NOP, has been shown to inhibit bronchoconstriction and cough in guinea-pig or cat by inhibiting tachykinin release. 2 The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 51 publications
(67 reference statements)
1
22
0
Order By: Relevance
“…HCl infusion. In addition to our previous findings in the guinea-pig (Rouget et al, 2004), we have shown that HCl induced plasma extravasation but also bronchoconstriction were significantly reduced by a pretreatment with N/OFQ (Okada et al, 2000;Rizzi et al, 2002). We have also shown that the effects of both agonists were abolished by the selective NOP receptor antagonist UFP-101 , suggesting that their preventive actions on vascular leakage and bronchoconstriction are exclusively due to NOP receptor activation and share common mechanisms.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…HCl infusion. In addition to our previous findings in the guinea-pig (Rouget et al, 2004), we have shown that HCl induced plasma extravasation but also bronchoconstriction were significantly reduced by a pretreatment with N/OFQ (Okada et al, 2000;Rizzi et al, 2002). We have also shown that the effects of both agonists were abolished by the selective NOP receptor antagonist UFP-101 , suggesting that their preventive actions on vascular leakage and bronchoconstriction are exclusively due to NOP receptor activation and share common mechanisms.…”
Section: Discussionsupporting
confidence: 73%
“…These results are in agreement with several lines of evidence indicating inhibitory actions of N/OFQ on sensory nerves in the guinea-pig, such as inhibition of the contraction of the isolated bronchus induced by EFS , of capsaicin-induced bronchoconstriction of isolated lung (Corboz et al, 2000), of airway microvascular leakage induced by i.oe. HCl (Rouget et al, 2004), or in human isolated bronchi, inhibition of airway hyperresponsiveness induced by beta2-adrenoceptor agonists (Faisy et al, 2003). In addition, in this study, we also showed that N/OFQ and [Arg 14 ,Lys 15 ]N/OFQ did not inhibit SP-induced bronchoconstriction and microvascular leakage in airways, suggesting that NOP agonists do not interact with postsynaptic neurokinin receptors, but exert their inhibitory effects on sensory nerves at presynaptic sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, nociceptin inhibits bronchoconstriction and the release of pro-inflammatory molecules in isolated bronchi from guinea-pigs [101,102]. Nociceptin inhibited the microvascular leakage induced by hydrochloric acid (HCl) infusion in the oesophagus of anaesthetised guinea-pigs and this effect was reversed by J-113397 [103]. This result suggests that ORL-1 agonists might have utility in cough, bronchoconstriction, and inflammation resulting from gastro-oesophageal acid reflux.…”
Section: Other Potential Uses For Orl-1 Agonistsmentioning
confidence: 69%
“…In the brain, there are dense NOP receptors in the medullar nucleus tractus solitarius [11], where pulmonary and extrapulmonary afferent fibers terminate and provide polysynaptic inputs to second-order neurons which modulate the respiratory neuron activities [186]. Recently, N/OFQ was found to inhibit airway microvascular leakage induced by intra-esophageal acid instillation [188]. The inhibitory effect of N/OFQ on acidinduced cough in guinea pigs may result from a decrease of peripheral C-fiber activity through an inhibition of the vallinoid receptor on airway-specific capsaicin-sensitive jugular ganglia [189].…”
Section: Coughmentioning
confidence: 99%